Alternate-Reality Lifestyles: Reconstructing Conspiracy Theories and Apocalypse Prepping in the Digital Era - McQueen, Scotty Tiger (Trinity College Dublin. School of Creative Arts. Discipline of Film, 2024)
This dissertation provides a theoretical basis for, and critical analysis of, two creative-practice projects conducted via social media platforms. These projects were designed to examine how – in an era marked by alternative information ecosystems, ubiquitous digital disinformation, and genuine collective existential threats – emergent and digitally-perpetuated counter-factual narratives can be ethically deconstructed and redirected toward socially constructive ends. The aim of this praxis was to reflexively and self-critically explore the gulf between surface and substance in digitally mediated disinformation and alternate-reality lifestyles; in which digital technologies increasingly allow for the intentional, inadvertent, or ironic blurring of boundaries between fiction and nonfiction. To this end, this praxis employs a hybridized creative-practice research methodology combining alterdisciplinarity (Bowman; 2008) with the triangulation of creative-practice, critical analysis, and civic engagement (Conquergood; 2002). Both projects were informed by original research, as well as by several established theories including guidelines for Deconstructing popular culture (Bowman; 2008) and the poetics of debunking proposed by the Wu Ming Foundation (2018) and endorsed by Henry Jenkins’ MacArthur Foundation-supported Civic Imagination Project (2018). Rather than directly challenge counter-factual narratives with facts or logic, these projects appropriate conspiracy theorist and doomsday “prepper” aesthetics in order to subvert harmful or violent premises common within such discourse. Both this dissertation and these creative-practice elements contribute to and expand the methodologies of alterdisciplinary intervention and the poetics of debunking. Ultimately, these projects demonstrate how data-supported and ethically- grounded interventions can be framed within the increasingly popular, but demonstrably problematic, discourse of conspiracy and apocalypse cultures.
Keywords: Creative practice and social media